Virtual Lab Experiment: Physics Educational Technology (PhET)Photo Electric Effect for Senior High School - Supurwoko Supurwoko; C Cari; Sarwanto Sarwanto; Sukarmin Sukarmin; Rini Budiharti; Tiarasita Summa Dewi (Universitas Sebelas Maret, 2017)
This paper introduced these Physics Educational Technology (PhET) Simulation and demonstrated their utility for Senior High School Students. The PhET simulations are very involved, interactive animated environments that create a unique opportunity for students. In each case, we demonstrate that discussion simulations are more productive, for developing student conceptual understanding for photo electric effect than traditional discussion without simulations. During the discussion with PhET simulation, students can construct their understanding about concepts photo electric effect within this framework. Students learn by building on their prior understanding through a series of constrained and supportives exploration. The simulations support an interactive approach and constrain students productively.